SOSIALISASI PENERAPAN KEBIJAKAN KAWASAN WAJIB MENCUCI TANGAN DENGAN PERILAKU PERSONAL HYGIENE PADA MASA PANDEMI DI DESA SIDOMULYO KECAMATAN SIBIRU-BIRU KABUPATEN DELI SERDANG - Jon Pitter Sinaga; Sri Pratiwi Sitio; Yunita Syahputri Damanik (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Correct hand washing behavior is one aspect that is an indicator in PHBS which is currently a worldwide concern. This is because not only in developing countries, but also in developed countries, there are still many people who forget to wash their hands properly. This shows that there is still a lack of hand washing practices or actions in the community. Based on the Health Service Program Survey on perceptions and behaviors towards hand washing habits, it was found that soap has reached almost every home in Indonesia, but around 3% of those who use soap for washing hands, in villages the figure is usually even lower. Covid-19 has changed people's perspective to start a new habit by regularly washing their hands. This is regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2014. One of the pillars in this movement is to use soap when washing hands. Article 3 paragraph 2 explains that the behavior of washing hands with soap can at least be realized through cultivating the behavior of washing hands using soap Soap with clean running water, it is hoped that this habit can continue for individuals, families, and communities in Sidomulyo Village, Sibiru-Biru District, Deli Serdang Regency.